Preparation and Investigation of Silver Nanoparticle⁻Antibody Bioconjugates for Electrochemical Immunoassay of Tick-Borne Encephalitis - Khristunova, Yekaterina; Korotkova, Elena; Kratochvil, Bohumil; Barek, Jiri; Dorozhko, Elena; Vyskocil, Vlastimil; Plotnikov, Evgenii; Voronova, Olesya; Sidelnikov, Vladimir (Sensors, 2019)
A new simple electrochemical immunosensor approach for the determination of antibodies to tick-borne encephalitis virus (TBEV) in immunological products was developed and tested. The assay is performed by detecting the silver reduction signal in the bioconjugates with antibodies (Ab@AgNP). Here, signal is read by cathodic linear sweep voltammetry (CLSV) through the detection of silver chloride reduction on a gold-carbon composite electrode (GCCE). Covalent immobilization of the antigen on the electrode surface was performed after thiolation and glutarization of the GCCE. Specific attention has been paid to the selection of conditions for stabilizing both the silver nanoparticles and their Ab@AgNP. A simple flocculation test with NaCl was used to select the concentration of antibodies, and the additional stabilizer bovine serum albumin (BSA) was used for Ab@AgNP preparation. The antibodies to TBEV were quantified in the range from 50 IU·mL-1 to 1600 IU·mL-1, with a detection limit of 50 IU·mL-1. The coefficient of determination (r2) is 0.989. The electrochemical immunosensor was successfully applied to check the quality of immunological products containing IgG antibodies to TBEV. The present work paves the path for a novel method for monitoring TBEV in biological fluids.
Keywords: Electrodes; Encephalitis Viruses, Tick-Borne; Encephalitis, Tick-Borne; klíšťová encefalitida; Spectrophotometry, Ultraviolet; viry klíšťové encefalitidy; elektrody; zvířata; kovové nanočástice; Silver; velikost částic; Cattle; Electrochemical Techniques; stříbro; Immunoassay; skot; sérový albumin hovězí; spektrofotometrie ultrafialová; protilátky virové; Serum Albumin, Bovine; Antibodies, Viral; Animals; imunoanalýza; elektrochemické techniky; Particle Size; Metal Nanoparticles